قياس وتقييم جودة الخدمات الصحية دراسة تطبيقية في الهيئة العامة لطب العيون في دمشق - الصرن رعد; الغرير عبير (Latakia University Journal - Economic and Legal Sciences Series, 2018)
توصلت دراستنا التي تهدف إلى التعرف على مدى اهتمام الهيئة العامة لطب العيون بعامل الجودة والشروط الواجب توفرها لتقديم خدمات بجودة أفضل، ومعيقات تحقيق ذلك، إلى أن الهيئة العامة لطب العيون تقدم مستوى جيد من الخدمات الصحية وذلك باعتماد مقياس جودة الخدمة (SERVQUAL Scale ) المكون من خمسة أبعاد رئيسية وهي : الملموسية، الاعتمادية، الاستجابة، التوكيد (الثقة)، التعاطف، لكنها يجب أن تعمل على تحديث التجهيزات المستخدمة وتقديم مزيدا من الدعم المادي والمعنوي للعاملين في المشفى لضمان استمرارية جودة الخدمة وعدم تأخرهم عن أداء عملهم. Our study which aim to identify the interest of the General Authority of Ophthalmology in quality factor and conditions that should be available to provide a best services, in addition to the obstacles, found that the General Authority of Ophthalmology offers a good level of health services through using a service quality scale (SERVQUAL Scale), which consists of five main dimensions, namely: tangibility, reliability, responsiveness, Assurance and empathy, but they should work on updating the used equipment and provide more financial and moral support for those working in the hospital to ensure continuity of service quality and avoiding performance backwardness